The impact of pain on the pharmacokinetics of transdermal flunixin meglumine administered at the time of cautery dehorning in Holstein calves. (November 2018) - Kleinhenz, Michael D.; Van Engen, Nicholas K.; Gorden, Patrick J.; Kleinhenz, Katie E.; Kukanich, Butch; Rajewski, Suzanne M.; Walsh, Philip; Coetzee, Johann F.
Abstract: Objective: To study the influence of pain on the pharmacokinetics and anti-inflammatory actions of transdermal flunixin administered at dehorning. Study design: Prospective, crossover, clinical study. Animals: A total of 16 male Holstein calves, aged 6–8 weeks weighing 61.3 ± 6.6 kg. Methods: Calves were randomly assigned to one of two treatments: transdermal flunixin and dehorning (PAIN) or transdermal flunixin and sham dehorning (NO PAIN). Flunixin meglumine (3.33 mg kg −1 ) was administered topically as a pour-on concurrently with hot iron dehorning or sham dehorning. The calves were subjected to the alternative treatment 14 days later. Blood samples were collected at predetermined time points up to 72 hours for measurement of plasma flunixin concentrations. Pharmacokinetics parameters were determined using noncompartmental analysis. Prostaglandin E2 (PGE2 ) concentration was determined using a commercial enzyme-linked immunosorbent assay. The 80% inhibition concentration (IC80 ) of PGE2 was determined using nonlinear regression. Pharmacokinetic data were statistically analyzed using paired t tests and Wilcoxon rank sums for nonparametric data. Flunixin and PGE2 concentrations were log transformed and analyzed using repeated measures. Results: A total of 15 calves completed the study. Plasma half-life of flunixin was significantly longer in PAIN (10.09 hours) than NO PAIN (7.16 hours) ( p  = 0.0202). Bioavailability of transdermal flunixin was 30% and 37% in PAIN and NO PAIN, respectively ( p  = 0.097). Maximum plasma concentrations of flunixin were 0.95 and 1.16 μg mL −1 in PAIN and NO PAIN, respectively ( p  = 0.089). However, there was a treatment (PAIN versus NO PAIN) by time interaction ( p  = 0.0353). PGE2 concentrations were significantly lower in the PAIN treatment at 48 and 72 hours ( p  = 0.0092 and p  = 0.0287, respectively). The IC80 of PGE2 by flunixin was similar in both treatments ( p  = 0.88). Conclusion and clinical relevance: Pain alters the pharmacokinetics and anti-inflammatory effects of transdermally administered flunixin.